SUSTAINABILITY OF CIRCULATION PATTERNS TO EASY MOBILITY VISITORS CASE STUDY: PALACE BANDUNG ELECTRONIC CENTER, BANDUNG - Susanto (Jurnal Riset Arsitektur, 2018)
Abstract- The addition of new buildings especially in the shopping center building is often the case, it aims to develop activities in old shopping buildings that are considered to have potential in maintaining or improving the quality of a shopping center, but the development can be a problem if in the initial development of a shopping center has no plans for adding or thinking about the second stage of development for some time to come. As a result, the designer must be able to create a connection circulation path in the building design that looks united between the old building and the new building into a unified whole, but there are several factors that must be adapted to the condition and state of the old building so that the resulting building can be continuous with each other.This research will discuss about the circulation inside the shopping center building, especially on the continuity between circulation pattern of old building and new building of shopping building. The object used is electronic shopping center Istana Bandung Electronic Center or often called BEC located at Jalan Purnawarman no 13-15, Bandung.Qualitative method is done by collecting data from object of study in the form of plan, documentation of picture or photo, study of literature, theories, and so on. Quantitative methods are carried out by listing the mobility of visitors within the building, especially in the path of meeting the circulation patterns between old and new buildings in the BEC shopping area.The purpose of this research is to know the continuity of circulation pattern between old building and new building as one shopping center, seen from the ease of visitor mobility inside the building, and to know and to evaluate the effectiveness of combined circulation pattern between old building and new building inside shopping area Istana Bandung Electronic Center. Key Words: continuity, circulation patterns, ease of visitor mobility, shopping center.